Authorea
DOI: 10.22541/au.158809451.14643742
|View full text |Cite
|
Sign up to set email alerts
|

The discernible and hidden effects of clonality on the genotypic and genetic states of populations: improving our estimation of clonal rates

Abstract: Partial clonality is widespread across the tree of life, but most population genetics models are designed for exclusively clonal or sexual organisms. This gap hampers our understanding of the influence of clonality on evolutionary trajectories and the interpretation of population genetics data. We performed forward simulations of diploid populations at increasing rates of clonality (c), analysed their relationships with genotypic (clonal richness, R, and distribution of clonal sizes, Pareto β) and genetic (FIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(28 citation statements)
references
References 71 publications
2
13
0
Order By: Relevance
“…The identification of repeated MLGs in addition to mean negative values of F IS , and significant linkage disequilibrium across loci observed in L. rodriguezii are features that all agree with signatures of clonality in natural populations (Balloux et al, 2003;. Nevertheless, we must be aware that inferring the rates of clonality by taking into account both the genotypic richness (R) and the average F IS values remains unachievable, except for high levels of clonality, greater than 95% (Balloux et al, 2003;Stoeckel et al, 2019), or requires the availability of temporal samples (Ali et al, 2016;Becheler et al, 2017). Furthermore, the estimates of R are strongly dependent on sampling strategy and density, basically decreasing with increasing sampling effort (Arnaud-Haond et al, 2007;Becheler et al, 2017;Gorospe et al, 2015).…”
Section: The Genomic Patterns Of Clonalitymentioning
confidence: 88%
See 4 more Smart Citations
“…The identification of repeated MLGs in addition to mean negative values of F IS , and significant linkage disequilibrium across loci observed in L. rodriguezii are features that all agree with signatures of clonality in natural populations (Balloux et al, 2003;. Nevertheless, we must be aware that inferring the rates of clonality by taking into account both the genotypic richness (R) and the average F IS values remains unachievable, except for high levels of clonality, greater than 95% (Balloux et al, 2003;Stoeckel et al, 2019), or requires the availability of temporal samples (Ali et al, 2016;Becheler et al, 2017). Furthermore, the estimates of R are strongly dependent on sampling strategy and density, basically decreasing with increasing sampling effort (Arnaud-Haond et al, 2007;Becheler et al, 2017;Gorospe et al, 2015).…”
Section: The Genomic Patterns Of Clonalitymentioning
confidence: 88%
“…Furthermore, the estimates of R are strongly dependent on sampling strategy and density, basically decreasing with increasing sampling effort (Arnaud-Haond et al, 2007;Becheler et al, 2017;Gorospe et al, 2015). In that context, recent studies reported that R had poor relevance for measuring the relative importance of sexual versus clonal reproduction (Arnaud-Haond et al, 2019), even using relatively large sample sizes (from 100 to 500 individuals) (Stoeckel et al, 2019). Therefore, we suspect that the genotypic richness (R) of L. rodriguezii was probably overestimated in our study, due to the complexity of sampling at these depths (i.e.…”
Section: The Genomic Patterns Of Clonalitymentioning
confidence: 99%
See 3 more Smart Citations